1995
DOI: 10.1248/cpb.43.1154
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Neuromedin U.II. Highly Potent Analogs Substituted or Modified at the N-Terminus of Neuromedin U-8.

Abstract: To develop a highly potent agonist and to examine the structure-contractile activity relationship of neuromedin U-8(NMU-8), seventeen analogs were synthesized and tested for contractile activity on isolated chicken crop smooth muscle preparations. The analogs were designed to examine the contributions of cyclic structure and acidic function at the N-terminal of NMU-8 and NMU-8(2--8) to the biological activity. The relative activity (RA) values of NMU-8 analogs were as follows: [Dp-Glu1]-NMU-8,5.50; [pyrohomogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…It is known that these structurally highly conserved neuropeptides share a motif of FLFRPRX-amide, suggesting the importance of this sequence in the interaction with its cognate receptors. Specifically, NMU-8 peptides precede with a large flexibility of the 4 amino acids sequence rich in hydrophobic residues, namely Tyr -NH 2 in all species, implying that an amphiphilic structure could be designed [23][24][25][26][27][28][29] . Diphenyl groups are widely present in many drugs on the market targeting GPCR, including adrenergic receptor antagonists, muscarinic receptor antagonists, analgesic agents (opioid receptor agonists), anti-allergic medications (histamine receptor-1 antagonists), and serotonin receptor modulators [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that these structurally highly conserved neuropeptides share a motif of FLFRPRX-amide, suggesting the importance of this sequence in the interaction with its cognate receptors. Specifically, NMU-8 peptides precede with a large flexibility of the 4 amino acids sequence rich in hydrophobic residues, namely Tyr -NH 2 in all species, implying that an amphiphilic structure could be designed [23][24][25][26][27][28][29] . Diphenyl groups are widely present in many drugs on the market targeting GPCR, including adrenergic receptor antagonists, muscarinic receptor antagonists, analgesic agents (opioid receptor agonists), anti-allergic medications (histamine receptor-1 antagonists), and serotonin receptor modulators [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Structural modifications Five groups of analogs to 101586 were designed and synthesized. Compounds 1a-d were designed based on the SAR information relative to porcine NMU-8 [23][24][25][26][27][28][29] . The diphenyl group was introduced to resemble the hydrophobic residues in this peptide, as we believe this group may bind to a hydrophobic site on the hNMU-R, and that an interaction with an anionic site of the receptor might be realized by linking to a cyclized guanidine group with changes in the carbon chain length and ring size.…”
Section: Hts Campaignmentioning
confidence: 99%
“…Presumably, changes in the N-terminal region alter the 3-dimensional structure of the peptide and favor a conformation with enhanced activity. Conversely, modification of the N terminus may result in increased resistance to degradation by peptidases, thereby increasing the peptide half-life (11,12 ). Lastly, posttranslational amidation of the C-terminal amino acid is also essential for NmU activity, because deamidated forms are unable to induce smooth muscle contraction or intracellular Ca 2ϩ influx (9,13,14 ).…”
Section: Structurementioning
confidence: 99%
“…1,2 In 1995, Hashimoto et al reported that N-terminal succinylated 1a, which was synthesized as an aminopeptidase-resistant derivative, showed potent contractile activity toward chicken crop smooth muscle expressing avian NMU receptors. 10 Recently, we performed a structure−activity relationship (SAR) study of heptapeptide 1a to develop receptor-selective agonists using cultured cells expressing human NMU receptors. As shown in Figure 1A, the results indicated that (1) the α-amino group at the N-terminal Phe 0 residue in 1a was not important for the agonistic activity because the N-terminal des-amino derivative, 1b, had similar activity to 1a; (2) N-terminal 3-pyridylpropionyl (1c) and 3-cyclohexylpropionyl (1d) structures were important for selective agonistic activities toward NMUR1 and NMUR2, respectively; (3) bulky aromatic amino acid residues, e.g., Trp and naphthylalanine (Nal), at residue 1 (Leu 1 ) were important for both agonistic activity and selectivity toward NMUR1; (4) aliphatic amino acids, e.g., Leu, at residue 2 (Phe 2 ), were important for both agonistic activity and selectivity toward NMUR2; and (5) α,β-diaminopropanoic acid (Dap) and α,γ-diaminobutyric acid (Dab) at residue 3 (Arg 3 ) led to higher agonistic activity and selectivity toward NMUR2.…”
mentioning
confidence: 99%